FORMULATION AND INVESTIGATION OF ANTIOXIDANT POTENTIAL OF O/W LOTIONS CONTAINING Tamarindus indica L. FRUIT PULP EXTRACT - Isnaini, Nadia; Songkro, Sarunyoo; Kaewnopparat, Nattha; Maneenuan, Duangkhae; Tanmanee, Niwan (MATTER: International Journal of Science and Technology, 2019)
The fruit pulp extracts of Tamarindus indica have been reported to possess several biological activities, especially antioxidant property which is suitable for cosmetic application. Therefore, the aims of this study were to formulate the tamarind fruit pulp extract loaded lotions (o/w emulsions), and to assess the antioxidant activity of tamarind fruit pulp extract loaded lotions. Initially, tamarind fruit pulp extracts were prepared by a solvent extraction method. The solvents used were water or a mixture of water and ethanol (water: ethanol= 1:1). Afterwards, the obtained tamarind fruit pulp extracts were subjected to lyophilization process. The tamarind fruit pulp extracts were tested for antioxidant activity by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay to determine suitable concentrations of the extracts to be incorporated into the lotions, which were 2 and 4%w/w in the current study. Apart from the basic ingredients of the oil phase and water phase, ViscOptima SE (2%w/w) was selected as an emulsifier and a thickener of the formulations. The tamarind fruit pulp extract loaded lotions were characterized for physicochemical property and antioxidant potential. The freshly prepared tamarind fruit pulp extract loaded lotions were light brown with homogeneity and no phase separation was observed after centrifugation at 3,000 rpm for 30 min. They had weak acidic pH (4.4-5.1), considered acceptable for skin application. The loaded formulations (F1, 2%w/w) and F2, 4%w/w)) exhibited significantly higher conductivity values than that of the unloaded formulation (F0) (p<0.05). The formulations behaved as pseudoplastic flows with low viscosity. The DPPH measurement revealed that the formulations F1 and F2 had potential antioxidant activity. In conclusion, topical o/w lotions containing tamarind fruit pulp extract were successfully prepared. They had substantial antioxidant activities. As a result, tamarind fruit pulp extract loaded lotions displayed a potential use in cosmetic formulations, especially antiaging products.